2016
DOI: 10.1002/art.39594
|View full text |Cite
|
Sign up to set email alerts
|

Risk of End‐Stage Renal Disease in Patients With Lupus Nephritis, 1971–2015: A Systematic Review and Bayesian Meta‐Analysis

Abstract: Objective End-stage renal disease (ESRD) is a major consequence of lupus nephritis, but how this risk has changed over time is unknown. We conducted this systematic review to examine changes in ESRD among adults with lupus nephritis from 1971 to 2015 and to estimate risks of ESRD among contemporary patients. Methods We searched PubMed, Embase, and the Cochrane Database of Systematic Reviews for cohort studies and clinical trials on ESRD in adults with lupus nephritis. We analyzed studies from developed and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
282
1
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 404 publications
(304 citation statements)
references
References 41 publications
7
282
1
14
Order By: Relevance
“…The risk of ESRD is higher in certain subsets of LN. For example, in class 4 LN the risk may be as high as 44% over 15 years (27). Patients with LN also have a higher standardized mortality ratio (6-6.8 versus 2.4) and die earlier than SLE patients without LN (28)(29)(30)(31).…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of ESRD is higher in certain subsets of LN. For example, in class 4 LN the risk may be as high as 44% over 15 years (27). Patients with LN also have a higher standardized mortality ratio (6-6.8 versus 2.4) and die earlier than SLE patients without LN (28)(29)(30)(31).…”
Section: Epidemiologymentioning
confidence: 99%
“…The increased exposure of LN patients to MMF has raised some concerns as to whether it is equivalent to cyclophosphamide induction with respect to longterm kidney outcomes (77). A recent meta-analysis showed that between the 1970s and the 1990s the risk of ESRD from LN declined and plateaued, and this was coincident with cyclophosphamide treatment becoming routine (27). In the 2000s, as MMF was becoming a dominant induction drug for LN, the risk of ESRD increased, and was highest at 44% over 15 years in patients with diffuse proliferative LN.…”
Section: Current Approaches To Treatmentmentioning
confidence: 99%
“…Renal involvement remains one of the important factors influencing management and long-term prognosis of pSLE (6)(7)(8)(9). There is some evidence that the prognosis of lupus nephritis in developing countries is worse than that in developed countries (10). Some studies from other parts of India have highlighted the long-term outcome in children with lupus nephritis (11,12), but there has been no detailed report from Eastern India.…”
Section: Introductionmentioning
confidence: 99%
“…Current immunosuppressive therapies for LN are both toxic and insufficiently effective, and a substantial number of patients progress to end stage renal disease and death 2,3 . Despite the rapid pace of immunologic discovery, most clinical trials of rationally designed therapies have failed in both general SLE and LN, and only one new drug has been approved for the treatment of SLE in the last 5 decades 2,4 .…”
mentioning
confidence: 99%